Risk assessment of deep excavation construction based on combined weighting and nonlinear FAHP - Liu, Shihao; Song, Zhanping; Zhang, Yong; Guo, Desai; Sun, Yinhao; Zeng, Tao; Xie, Jiangsheng (Frontiers in Earth Science, 2023)
In the risk assessment of deep excavation construction using fuzzy analytic hierarchy process (FAHP), the weight results obtained by subjective weighting method are greatly influenced by the subjective factors of evaluators, and the use of linear operators to calculate risk levels can lead to a weakening effect on the impact of prominent risk factors, resulting in poor rationality of excavation risk evaluation results. To address these issues, this paper proposes a deep excavation construction risk assessment model based on combination weighting and nonlinear FAHP. The WBS-RBS method is used to guide the construction of the risk assessment indicator system for deep excavation construction, and the combination weight value is obtained by combining subjective and objective weights through game theory combination weighting method. The fuzzy relationship matrix is constructed based on the membership degree vector obtained from expert evaluation, and the nonlinear operator is introduced for comprehensive calculation. Based on the principle of maximum membership degree, the final risk level of excavation construction is obtained. The new model is applied to the risk analysis of the Rongmin Science and Innovation Park project in Xi'an, and the excavation construction risk level of this area is determined to be level 2, indicating relatively low risk. Based on the case study of the deep excavation engineering in the Rongmin Science and Innovation Park project, differences between the new model and the FAHP evaluation method are discussed, further verifying the reliability of the new model.